2019
DOI: 10.18553/jmcp.2019.25.3-b.s1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Treatment Patterns and Costs in Patients with Prostate Cancer and Bone Metastases

Abstract: Field Data Generation and Observational Studies team. In this role, Wen is responsible for leading the development and implementation of U.S. Data Generation and Observational Studies research in the field. In addition, she leads the dissemination and communication of health economics and outcomes data for health plans, integrated delivery networks, and other health care systems such as the Department of Veterans Affairs Medical Centers. Wen has a bachelor of science degree in pharmacy, a master of science deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 20 publications
2
36
1
Order By: Relevance
“…Similar treatment patterns were observed by Seal et al in a hospital database study . However, for the specific drugs used in each class of treatment, patterns found in our study differed from that in a US population, mainly because newer agents such as abiraterone, denosumab, radium‐233, and sipuleucel‐T were neither approved nor reimbursed in China during the study period and so were not captured in the database.…”
Section: Discussionsupporting
confidence: 69%
“…Similar treatment patterns were observed by Seal et al in a hospital database study . However, for the specific drugs used in each class of treatment, patterns found in our study differed from that in a US population, mainly because newer agents such as abiraterone, denosumab, radium‐233, and sipuleucel‐T were neither approved nor reimbursed in China during the study period and so were not captured in the database.…”
Section: Discussionsupporting
confidence: 69%
“…A recent study, using real-world data from patients with chemotherapy-naïve mCRPC in a commercially insured population, reported lower HCRU and PC-related inpatient and emergency department costs for enzalutamide compared with abiraterone [ 18 ]. Another recent real-world study described treatment patterns, healthcare costs, and survival in patients with mCRPC who were commercially insured or Medicare covered and showed that enzalutamide and abiraterone were the most common first-line treatments (more than 65% in total); however, no direct cost comparisons between the treatments were reported [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…As claims data are routinely collected for billing and reimbursement, information on clinical parameters, such as cancer stage or tumor type, were not available for patient selection or cost stratification. Moreover, as already stated [32], we did not find a completely validated algorithm identifying patients with mCRPC in the literature. However, consulting a clinical expert, we developed an algorithm identifying patients with PC, metastasis, castration resistance, and second-line treatment, using a wide range of different classification systems for claims data.…”
Section: Discussionmentioning
confidence: 74%